The Effect of Combined Resistance and Endurance Training on Some Physical Fitness Factors in Young Men - Beni, Mohsen Akbarpour; Sadeghian, Hamid (Journal of Sports Research, 2015)
The aim of this study was to investigate the effect of an eight-week combined resistance and endurance training program on the body composition (total body water percentage, fat free body mass and body fat percentage) and aerobic power of young men. Fifty young men students with the age mean of 21.18±2.1, height mean of 176.34±4.1 and weight mean of 70.1±5.4 were randomly divided to five combined endurance- resistance (n=10), combined resistance-endurance (n=10), resistance (n=10), endurance (n=10) and control (n=10) groups. In three sessions (week 0, week 4 and week 8), their aerobic power and body composition were measured in order to obtain their maximum oxygen consumption, total body water percentage, fat free body mass and body fat percentage. Then, the training groups performed their training programs for eight weeks, three sessions per week. The training program of the resistance group included circular resistance. The endurance group performed running with 70-80% maximum heart rate for 20-26 min. The program of the combined endurance-resistance group was composed of doing endurance training first and resistance training next and that of the combined resistance-endurance group included performing resistance training first and endurance training next. The control group did not participate in any training program during the research period. The research data were analyzed using Analysis of Variance (ANOVA) with repeated measures along with dependent t test considering the Bonferroni's P correction for within group evaluation and one way Analysis of Variance (ANOVA) along with Tukey’s post hoc test for between group evaluation (> α0/05). The results showed that eight weeks of endurance training, combined endurance-resistance training and combined resistance-endurance training significantly increased the maximum oxygen consumption (P<0.05). Also, total body water percentage significantly increased after eight weeks of resistance, endurance, combined endurance-resistance and combined resistance-endurance training (P< 0.05). Fat free body mass increased in the combined endurance-resistance, combined resistance-endurance and resistance groups; however, this increase was only significant in the resistance group. Body fat percentage had significant decrease in the four experimental groups but this decrease was more evident in the combined endurance-resistance and combined resistance-endurance groups compared with the resistance and endurance groups (P<0.05).Considering the research findings, people can perform combined resistance-endurance training in order to highly decrease their body fat percentage. In sum, it can be concluded that doing combined resistance-endurance training is more helpful for decreasing fat and controlling weight and this kind of combined training can be recommended to people.